Bariatric surgery and birth defects: A systematic literature review. Issue 6 (11th October 2018) - Benjamin, Renata H.; Littlejohn, Sarah; Mitchell, Laura E.
Abstract: Background: Bariatric procedures are on the rise. The risk of birth defects in pregnancies following such procedures may be increased (eg, due to nutrient deficiencies) or decreased (eg, due to decreased maternal body mass index, BMI). Methods: We conducted a systematic literature review of the association between bariatric surgery and birth defects using Ovid MEDLINE and PubMed (1946‐2017). Information was abstracted on study design, exposures, outcomes, covariates and estimates of association. Results: Fifteen studies met our inclusion criteria: 14 evaluated the outcome of any birth defect, and one evaluated neural tube defects. Estimates of association between bariatric surgery and birth defects were available for nine studies and ranged from 0.6 to 1.9 (all 95% confidence intervals included 1.0). When studies were stratified by surgery type, there was no obvious pattern of association. When stratified by the approach used to account for BMI, positive associations were observed in studies that did not account for maternal prepregnancy BMI or used women with normal BMI as the reference group (range: 1.3‐1.9). Estimates from studies that either matched or adjusted for prepregnancy BMI were closer to the null (range: 1.1‐1.2) and studies that compared to morbidly obese women reported protective associations (range: 0.6‐0.7). Conclusions: Studies of the association between bariatric surgery and birth defects vary with respect to the surgical procedures included, birth defects ascertainment methods and approaches used to account for maternal BMI. Consequently, it is not possible to draw a conclusion regarding the association between bariatric surgery and birth defects. Additional studies are warranted.